Infliximab biosimilar CT-P13 therapy is effective and safe in maintaining remission in Crohn's disease and ulcerative colitis – experiences from a single center. (2nd November 2017) - Farkas, Klaudia; Rutka, Mariann; Ferenci, Tamás; Nagy, Ferenc; Bálint, Anita; Bor, Renáta; Milassin, Ágnes; Fábián, Anna; Szántó, Kata; Végh, Zsuzsanna; Kürti, Zsuzsanna; Lakatos, Péter L.; et al.
ABSTRACT: Background : CT-P13, the first biosimilar monoclonal antibody to infliximab (IFX), has been confirmed to be efficacious in inducing remission in inflammatory bowel diseases (IBD). The aim of this study was to evaluate the long-term efficacy and safety of CT-P13 therapy in Crohn's disease (CD) and ulcerative colitis (UC), and to identify predictors of sustained clinical response during a 54-week CT-P13 treatment period. Patients and methods : Patients with CD and UC, who were administered CT-P13, were prospectively enrolled. Clinical response was assessed at week 14 and week 54. Predictive factors for disease outcome at week 54 were evaluated. Results : 57 CD and 57 UC patients were included; 55 CD and 49 UC patients completed the induction therapy and 50 CD and 46 UC patients completed the 54-week treatment period. Clinical remission was achieved in 65.5% of CD and 75.5% of UC patients at week 14. Rate of continuous clinical response was 51% in both CD and UC at week 54. None of the examined parameters were predictive to the clinical outcome neither in CD, nor in UC. Conclusion : This study confirmed the long-term efficacy and safety of CT-P13 therapy in IBD. Response rates at week 54 were similar in CD and UC.